The relationship between emotional intelligence and leadership effectiveness among managers in BERNAMA / Syazwani Mazuki and Izaidah Seman - Mazuki, Syazwani; Seman, Izaidah (2015)
The purpose of this study is to investigate the relationship between Emotional Intelligence (EQ) and leadership effectiveness among managers in Malaysian National News Agency (BERNAMA). This study is to look forward about the degree of emotional intelligence that can impact leadership effectiveness among managers in BERNAMA. Emotional Intelligence is one important factor especially to managers in order to handle and know their level of self-management, relationship-management and communication in an organization. The study is to see whether EI can improve the effectiveness of leadership among managers. This study is involving all managers in every department in BERNAMA, who will become our respondent. The researcher used questionnaire and distributes it to the managers in order to collect the information regarding this research.